ORGANIZATIONAL FOUNDATIONS OF THE PRACTICAL IMPLEMENTATION OF PEDAGOGICAL INNOVATIONS - Ortiqova Nargiza Akramovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the organizational foundations of the practical implementation of pedagogical innovations.